Help! A vampire's coming! - Klein, Abby.; McKinley, John, 1956- (New York : Blue Sky Press, 2005)
When first-grader Freddy is exhausted because of nightmares, his friends and family give him suggestions on how to deal with them.
Go to sleep! -- Exhausted -- Your worst nightmare -- Secret mission -- Vampires, beware! -- That plan stinks -- Lock 'em up! -- Scratch, scratch -- Liars! -- Dream police to the rescue -- Freddy's fun pages.
edited hb 2015-06-16
Keywords: Bedtime -- Fiction; Nightmares -- Fiction